Tipologi Yesus Selaku Guru Transformator berdasarkan Perspektif Injil Matius - Hartono, Tri (STT Bala Keselamatan Palu, 2024)
Abstract: Most of the people believe that teachers are the people responsible for improving the nation. Jesus Christ, in the Gospel of Matthew, is described as an extraordinary teacher. His teachings are not only informative, but also transformative, capable of changing the lives of his followers. This research aims to explore the typology of Jesus as a transformative teacher in the Gospel of Matthew. This research uses qualitative methods, with text analysis of the Gospel of Matthew. Data was collected through identification and analysis of engagements that demonstrate Jesus' role as a transformative teacher. The analysis results show that Jesus used various teaching methods to transform his followers. Jesus Christ is described as an extraordinary transformative teacher in the Gospel of Matthew. His diverse and powerful teaching methods can change the lives of his followers and lead them into the Kingdom of God. This typology of Jesus as a transformative teacher has important implications for the understanding and application of Christian faith today. Abstrak: Sebagian besar orang percaya bahwa guru adalah orang yang bertanggung jawab untuk meningkatkan bangsa. Yesus Kristus, dalam Injil Matius, digambarkan sebagai guru yang luar biasa. Ajaran-ajarannya tidak hanya bersifat informatif, tetapi juga transformatif, mampu mengubah hidup para pengikutnya. Penelitian ini bertujuan untuk mengeksplorasi tipologi Yesus sebagai guru transformatif dalam Injil Matius.Penelitian ini menggunakan metode kualitatif, dengan analisis teks terhadap Injil Matius. Data dikumpulkan melalui identifikasi dan analisis perikatan-perikatan yang menunjukkan peran Yesus sebagai guru transformatif. Hasil Analisis menunjukkan bahwa Yesus menggunakan berbagai metode pengajaran untuk mentransformasi para pengikutnya. Yesus Kristus digambarkan sebagai guru transformatif yang luar biasa dalam Injil Matius. Metode pengajaran-Nya yang beragam dan penuh kuasa mampu mengubah hidup para pengikutnya dan menuntun mereka ke dalam Kerajaan Allah. Tipologi Yesus sebagai guru transformatif ini memiliki implikasi penting bagi pemahaman dan penerapan iman Kristen di masa kini